The Effect of Rainwater Quality on The Methane Concentration - Lilik S. Supriatin; Waluyo E. Cahyono; Syafrizon Syafrizon (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2017)
Research on the effect of pH of rainfall on the emission of methane (CH4) has been made. And what about the influence of the pH of rainfall at a concentration of CH4? That question will be answered through this research. The problem in this research is not yet known and the effect of the interaction of water quality in these clouds pH (degree of acidity) of rain on the concentration of CH4. The purpose of the study was the first object to determine acid rain in research location and to determine and analyze the influence of the pH of rainfall on the CH4 concentration. The research location is at Balai Pengamat Atmosfer dan Antariksa LAPAN in Kototabang hills, West Sumatra. The data used in this study is the pH of rainfall and CH4 concentrations. The analytical method used is the analysis of statistical and descriptive analysis. The results showed a correlation coefficient between the pH of rainfall with CH4 concentration of 0,87. The correlation coefficient indicates that the effect of the pH of rainfall is linearly proportional to the concentration of CH4. This means that the pH of rainfall is higher, then the CH4 concentration will increase.